miR-615 facilitates porcine epidemic diarrhea virus replication by targeting IRAK1 to inhibit type III interferon expression - Zheng, Hong-qing; Li, Cheng; Zhu, Xiao-fu; Wang, Wei-Xiao; Yin, Bao-ying; Zhang, Wen-juan; Feng, Shu-lin; Yin, Xun-hui; Huang, He; Zhang, Yan-ming (Frontiers in Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) in the Coronavirus family is a highly contagious enteric pathogen in the swine industry, which has evolved mechanisms to evade host innate immune responses. The PEDV-mediated inhibition of interferons (IFNs) has been linked to the nuclear factor-kappa B (NF-κB) pathway. MicroRNAs (miRNAs) are involved in virus–host interactions and IFN-I regulation. However, the mechanism by which the PEDV regulates IFN during PEDV infection has not yet been investigated in its natural target cells. We here report a novel mechanism of viral immune escape involving miR-615, which was screened from a high-throughput sequencing library of porcine intestinal epithelial cells (IECs) infected with PEDV. PEDV infection altered the profiles of miRNAs and the activities of several pathways involved in innate immunity. Overexpression of miR-615 increased PEDV replication, inhibited IFN expression, downregulated the NF-κB pathway, and blocked p65 nuclear translocation. In contrast, knockdown of miR-615 enhanced IFN expression, suppressed PEDV replication, and activated the NF-κB pathway. We further determined that IRAK1 is the target gene of miR-615 in IECs. Our findings show that miR-615 suppresses activation of the NF-κB pathway by suppressing the IRAK1 protein and reducing the generation of IFN-IIIs, which in turn facilitates PEDV infection in IECs. Moreover, miR-615 inhibited PEDV replication and NF-κB pathway activation in both IECs and MARC-145 cells. These findings support an important role for miR-615 in the innate immune regulation of PEDV infections and provide a novel perspective for developing new treatments.